The Endometriosis - treatment and new methods - Chrzanowski, Jakub; Ostaszewska, Sandra; Augustynowicz, Kinga; Szymańska, Ewa; Świąder, Kinga (Journal of Education, Health and Sport, 2023)
Introduction: Endometriosis is a common disease, especially in young women. In this article, we reviewed the epidemiology, symptoms, and various options for the treatment of endometriosis. Material and methods: The work was based on medical articles collected in PubMed, websites and medical books. The research was conducted by looking at keywords such as: "endometriosis", „endometriosis treatment”, „endometriosis and new methods" Results: There are many methods of treating endometriosis, ranging from hormonal therapy to surgical treatment. Conclusions: Endometriosis is difficult disease to treat. We need more researches and experience to find the perfect way treatment without side effects.